Short wavelength automated perimetry and standard automated perimetry in central serous chorioretinopathy - Han Peng Zhou (Nature Portfolio, 2020)
Abstract Short wavelength automated perimetry (SWAP) is known for detecting the early reduction of retinal sensitivity (RS) in glaucoma. It’s application in retinal diseases have also been discussed previously. We investigated the difference in RS measured between standard white-on-white automated perimetry (WW) and blue-on-yellow SWAP in central serous chorioretinopathy (CSC). The overall RS (W-RS, S-RS) as well as the RS inside and outside of the serous retinal detachment (SRD) region were investigated in 26 eyes of 26 CSC patients using WW and SWAP. The central retinal thickness, central choroidal thickness, SRD area (SRDa), and SRD height at the fovea were measured using optic coherence tomography. RS inside the SRD region was lower than that of outside for both perimetries (both p < 0.001). The difference between RS inside and outside of the SRD region was greater in SWAP compared to WW (p < 0.001). Univariate analysis revealed significant correlations between SRDa and both W-RS and S-RS (both p < 0.001); moreover, multivariate analysis indicated that only S-RS was selected as the optimal model for SRDa. Our study demonstrated that SWAP was detected the decrease in RS more accurately than WW in CSC. These results may suggest the usefulness of SWAP for detecting change of retinal function in CSC.